2000
DOI: 10.1172/jci10508
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte stem cells: targets for cutaneous carcinogens

Abstract: Figure 1Cross section of the epidermis demonstrating the epidermis (e) overlaying the dermis (d), and a hair follicle (hf) together with its sebaceous gland (sg). Original magnification, ×400.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 18 publications
2
84
0
Order By: Relevance
“…Epidermal stem cells that reside in a specific area of hair follicles were hypothesized to be target cells for skin carcinogenesis (Morris, 2000). We revealed that there was 25% reduction in the number of hair follicles in dorsal skin of K5-GR/ras+ transgenics (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…Epidermal stem cells that reside in a specific area of hair follicles were hypothesized to be target cells for skin carcinogenesis (Morris, 2000). We revealed that there was 25% reduction in the number of hair follicles in dorsal skin of K5-GR/ras+ transgenics (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…TPA administration stimulates papilloma formation even when started a year after DMBA treatment, suggesting that the initial mutation arises in long-lived SCs (Morris et al 1986(Morris et al , 1997Morris 2000). The demonstration that tumors can form, although at lower frequency, when the IFE is removed by dermabrasion after DMBA and repaired by HF cells suggests that cancer-initiating cells may reside in the IFE as well as in HFs (Argyris and Slaga 1981).…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…In order for latent neoplastic cells to persist in the skin, they must be slowly cycling to avoid removal to the suprabasal layers and loss by terminal differentiation, and they must reside within a protected niche or microenvironment within the skin (Lavker and Sun, 2000). Therefore, carcinogen target cells possess some qualities of a stem cell population (Morris, 2000). The most likely repository of keratinocyte stem cells (KSC) in the skin is the bulge region, which is located in the permanent portion of the hair follicle below the sebaceous gland at the point of attachment of the arrector pili muscle.…”
Section: Cellular Aspectsmentioning
confidence: 99%